{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# Chapter_11.2 - Chapter 11.2 Page 595(i ex = ex Example(A...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 11.2 Page 595. ' (i) ex = ex ( ) Example: (A) Find the derivatives for f ( x) = 4 x + 3e x ( ) 4 f ' ( x) = [ 4 x + 3e x ]' = 4 4 x + 3e x = 4 4 x + 3e (B) f ( x) = ex x3 ( ( ) 4 x 3 ) ( ) ( 4 x + 3e ) 3 x ' (4 + 3e x ) = (16 + 12e x ) 4 x + 3e x ( Chain _ Rule ) 3 f ' ( x) = (e x )' x 3 - e x ( x 3 )' Quotient _ Rule (x3 )2 = (e x ) x 3 - e x (3 x 2 ) e x x 2 ( x - 3) e x ( x - 3) = = x6 x6 x4 u ( x) ' (ii) (e ) = e u ( x ) u ' ( x) Find the derivatives for 2 Example: (A) f ( x) = e x 2 f ' ( x) = (e x )' = e x ( x 2 )' = 2 xe x (B) f ( x) = 10 + 5e -2 x 2 2 Rewrite f ( x) = 10 + 5e -2 x = 10 + 5e - 2 x f ' ( x) = [ 10 + 5e -2 x = ( ) 1 2 first! 10 + 5e - 2 x ( ) 1 2 ' = 1 10 + 5e -2 x 2 - 1 2 1 2 ( ) 1 -1 2 ( ) ' 1 10 + 5e -2 x 2 1 = 10 + 5e -2 x 2 ( ( ) ) (10)'+ (5e -2 x ) ' = ( ( ) 1 10 + 5e - 2 x 2 ( ) ) - 1 2 5 -2e - 2 x = - 5e -2 x ( ) - - 10e -2 x = -5e -2 x 10 + 5e -2 x ) ( - 1 2 (10 - 5e ) -2 x 1 Page 597. (i) ( ln x ) ' = 1 ; x (ii) ( ln u ( x) ) ' = 1 u ' ( x) ; u ( x) Page 736. Example: (A) Find the derivatives for 4 f ( x) = ( ln x ) 4 1 4( ln x ) f ' ( x) = [( ln x ) ]' = 4 ( ln x ) ( ln x ) = 4( ln x ) = x x 3 ' 3 3 (B) y = x 2 ln x y ' = ( x 2 ln x)' = ( x 2 )' ln x + x 2 (ln x )' Product Rule 1 = (2 x ) ln x + x 2 = 2 x ln x + x x Example: (A) Find the derivatives for g ( x) = ln(1 + x 2 ) 1 2x (1 + x 2 )' = 2 (1 + x ) (1 + x 2 ) g ' ( x ) = [ln(1 + x 2 )]' = (B) y = ln x 4 y ' = (ln x 4 )' = Page 598. Remark: 1 1 4 ( x 4 )' = 4 (4 x 3 ) = 4 x x x Change of basis ln b ln a y = log a b if and only if y = 2 Example: (A) Find the derivatives for f ( x) = log 2 x ln x ln 2 Rewrite f ( x) = log 2 x = ' 1 1 1 1 ln x f ' ( x) = (ln x )' = = = ln 2 x x ln 2 ln 2 ln 2 (B) f ( x) = log(1 + x 3 ) , here the base is 10 ln(1 + x 3 ) ln 10 Rewrite f ( x) = log(1 + x 3 ) = ' ln(1 + x 3 ) 1 1 1 3 ' 3 f ' ( x) = ln 10 = ln 10 ln(1 + x ) = ln 10 (1 + x 3 ) (1 + x )' Chain Rule 1 1 3x 2 = (3 x 2 ) = ln 10 (1 + x 3 ) (1 + x 3 ) ln 10 ( ) Additional Examples: Find the derivative for Example 1: f ( x) = x( ln x ) 2 1 2 2 f ' ( x) = ( x)' ( ln x ) + x[(ln x) 2 ]' = ( ln x ) + x [2 ln x ] = (ln x) 2 + 2 ln x x f ( x) = (5 - ln x) 4 Example 2: f ' ( x) = [(5 - ln x) 4 ]' = 4 (5 - ln x) 3 (5 - ln x) ' Chain Rule 1 4(5 - ln x ) 3 = 4 (5 - ln x) 3 (- ) = - x x Example 3: f ( x) = x ln x - x 1 - 1 = ln x + 1 - 1 = ln x x f ' ( x) = ( x ln x )'-( x)' = ( x)' ln x + x(ln x )'-1 = ln x + x 3 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online